Urgensi Bahasa Arab dalam Islam dan Dunia Internasional - Mohammad Zaki (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2023)
Language as a communication tool and interaction tool that is only owned by humans, language can be studied internally and externally. Arabic is synonymous with the language of Islam. Indonesian people learn Arabic only to deepen the Islamic religion. This is very common, considering that Islam was revealed in Arab countries and the language used in worship is also Arabic, and the Al-Qur'an and hadith which serve as guidelines for adherents are also in Arabic. So it is very natural that learning Arabic focuses more on how to understand the Qur'an, hadith, classic books that discuss Fiqh, Interpretation and other sciences related to Islam. Along with the development of the times, Arabic is no longer only studied for the sake of religion alone, this is evidenced by the existence of Arabic language faculties which are not only in Islamic-based universities, but also in several public universities, both in Indonesia and abroad. offers Arabic as a superior program offered to students. This research aims to explore the Arabic language perspective in Islam and the international world. Library research is used as a methodology in this research, with various data sourced from books and scientific journals related to the topic. The results of this research state that the stigma of Arabic as the language of the Islamic religion cannot be separated from the role of Arabic as a source language and Islamic doctrine. International political developments require Arabic to become a language across Arab countries, religions and certain identities. Arabic is now able to compete with other international languages, so that in the future the orientation of learning Arabic will not be limited to the religious dimension, but all dimensions of international life.